2017
DOI: 10.1039/c6cc09509g
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy towards the synthesis of a room-temperature discotic nematic liquid crystal employing triphenylene and pentaalkynylbenzene units

Abstract: A new approach is reported for the design of a room-temperature discotic nematic (N) liquid crystal (LC) dimer consisting of a triphenylene and a pentaalkynylbenzene unit linked via flexible alkyl spacers. The formation of the N phase is realized most likely through folding of the dimeric molecule that prevent stacking between the triphenylene units, as suggested by modelling in the mesophase derived from X-ray scattering results and high-level DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…In the present case, the observed Col h phase of the T‐M dyad connected with semi‐flexible spacers is similar to that of the T‐T and T‐PE systems connected with flexible spacer as reported earlier ,. However, we recently reported that T‐M system when connected only via flexible alkyl spacers, exhibits N D phase . This different phase behaviour can be explained as follows: T unit generally self assembles into Col h phase whereas M unit tends to form N D phase.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the present case, the observed Col h phase of the T‐M dyad connected with semi‐flexible spacers is similar to that of the T‐T and T‐PE systems connected with flexible spacer as reported earlier ,. However, we recently reported that T‐M system when connected only via flexible alkyl spacers, exhibits N D phase . This different phase behaviour can be explained as follows: T unit generally self assembles into Col h phase whereas M unit tends to form N D phase.…”
Section: Resultssupporting
confidence: 89%
“…When the linking spacer is flexible, then it forms possibly a folded disc and thus minimizes the energy by gaining the entropy while reducing the excluded volume through π‐π interactions between T and M units. These folded discs leads to an improper packing resulting into the formation of a N D phase . On the other hand, T and M unit will tend to be in a plane when they are connected with semi‐flexible spacer because folding will cost much more energy than entropy gain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have reported a new approach for the design of a room‐temperature N D LC dimer consisting of a TP and a PA unit linked through flexible alkyl spacers. The formation of the room‐temperature N D phase is likely due to folding of the dimer, which prevents π–π stacking among the composite disc units . In this communication, we have developed another new strategy to obtain a room‐temperature N D phase over a wide temperature range by connecting four PA units to an azobenzene core through flexible alkyl spacers.…”
Section: Introductionmentioning
confidence: 99%
“…For discotic dimers, the edge‐on conformation could be of two types, namely, folded‐ and unfolded‐form as shown in Figure C. Particularly, if the two discotic cores of the dimer are connected by flexible spacer, they tend to fold due to the strong π‐π interactions . In the present work, the TpImTp dimer molecule is symmetric and the experimentally observed A o values only indicate an edge‐on conformation without clarifying whether or not it is folded.…”
Section: Resultsmentioning
confidence: 61%